Former Homeland Areas and Unemployment in South Africa: A Decomposition Approach - Prudence Kwenda; Miracle Benhura; Gibson Mudiriza (Institute of Labor Economics (IZA), 2020)
This study estimates and decomposes the unemployment rate gap between former and non-former homeland areas in South Africa. We apply the Oaxaca-Blinder (1973) decomposition technique to the 2011 population census community profiles at main place level to identify the factors underpinning observed spatial patterns in unemployment. Results indicate that former homeland areas suffer from relatively higher rates of unemployment compared to non-former homeland areas. The 24%-point difference is primarily explained by differences in endowments. If main-place observed characteristics are equalised between former and non-former homeland areas, the unemployment gap can be reduced by as much as 80%. Factors driving the endowment effect are area compositional differences in age, gender, race, marital status and education. While the bulk of these factors are structural in nature, interventions that improve education attainment in former homeland areas and those that are sensitive to the challenges faced by black South African youth and women in the labour market will contribute immensely towards alleviating the spatial gap.
Keywords: N37; J01; 330; unemployment; former homeland area; decomposition and South Africa